Lombard Speech in Noise and Reverberation between Thai and English - Channakan Chaisittirerkkul; Nachanant Chitanont; Nao Hodoshima (My University, 2024)
In large indoor public spaces such as train stations, airports, hospitals, and shopping malls, the public address (PA) system transfers an important announcement whether during normal or emergencies. At times, the announcement made through the PA system was not intelligible enough to understand due to reverberation, echoes, and environmental noise (i.e., airplanes, trains, cars, and noise from humans) in the spaces, especially for older adults, people with hearing-related diseases, or non-native listeners. This study investigates whether adapting the Lombard effect to simulate an indoor PA system environment affects speech intelligibility in Thai and English. Sentences have been recorded with normal and Lombard speech in Thai and English. Eighteen Thai-native speakers between 19 and 23 years old participated in this experiment. The statistical result showed that adapting the Lombard effect to simulate an announcement in a large indoor PA system has no statistically significant difference in speech intelligibility compared to normal speech; no statistically significant interaction between language and speaking condition; and a statistically significant difference between Thai and English on speech intelligibility. Future research will aim to make the stimuli more realistic, explore different speaking styles, and speakers (male or female).
Keywords: Phonetics and Phonology Research; Linguistic Variation and Morphology; Speech and Audio Processing